Tinjauan Tanda Visual Yogyakarta Dalam FTV ‘Ada Cinta Diantara Kita’ - Danu Widiantoro; Siti Lenggogeni (LP2M Sekolah Tinggi Seni Rupa dan Desain Visi Indonesia (STSRD VISI), 2017)
Film is one part of creative economic development in Indonesia. FTV is one form of film development that lifts the story of everyday life into a glass screen. FTV entitled